2017
DOI: 10.1186/s12917-017-1150-0
|View full text |Cite
|
Sign up to set email alerts
|

African swine fever virus infection in Classical swine fever subclinically infected wild boars

Abstract: BackgroundRecently moderate-virulence classical swine fever virus (CSFV) strains have been proven capable of generating postnatal persistent infection (PI), defined by the maintenance of viremia and the inability to generate CSFV-specific immune responses in animals. These animals also showed a type I interferon blockade in the absence of clinical signs. In this study, we assessed the infection generated in 7-week-old CSFV PI wild boars after infection with the African swine fever virus (ASFV). The wild boars … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 57 publications
2
29
0
1
Order By: Relevance
“…Consequently, considering the low CD4/CD8 ratio and the reduced impact of the cytokine storm phenomenon, at least in terms of IFN-α, evidenced in CSFV persistently infected animals after super-infection with CSFV or African swine fever virus (Cabezón et al, 2017;Muñoz-González et al, 2016); we suggest the possible implication of the immune exhaustion mechanism that may favour the constant and high CSFV replication levels during CSFV persistence (Cabezón et al, 2017;Muñoz-González et al, 2016). Nevertheless, further studies will be performed to clarify the role of the immune exhaustion phenomenon and other immunosuppressive disorders in the CSFV pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, considering the low CD4/CD8 ratio and the reduced impact of the cytokine storm phenomenon, at least in terms of IFN-α, evidenced in CSFV persistently infected animals after super-infection with CSFV or African swine fever virus (Cabezón et al, 2017;Muñoz-González et al, 2016); we suggest the possible implication of the immune exhaustion mechanism that may favour the constant and high CSFV replication levels during CSFV persistence (Cabezón et al, 2017;Muñoz-González et al, 2016). Nevertheless, further studies will be performed to clarify the role of the immune exhaustion phenomenon and other immunosuppressive disorders in the CSFV pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have shown that the levels of sCD163 can be increased as a result of tissue damage during acute infection with highly pathogenic viruses, such as the African swine fever virus (ASFV) [39,40]. In addition, increased IFN-γ levels have also been found as part of the cytokine storm phenomenon responsible for the pathogenesis of ASFV [39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have shown that the levels of sCD163 can be increased as a result of tissue damage during acute infection with highly pathogenic viruses, such as the African swine fever virus (ASFV) [39,40]. In addition, increased IFN-γ levels have also been found as part of the cytokine storm phenomenon responsible for the pathogenesis of ASFV [39][40][41]. In agreement with the haemorrhagic lesions and levels of viral replication found in foetuses infected with the high virulence CSFV Margarita strain, it is likely that the increase of IFN-γ and sCD163 may be associated with the exacerbated immune response in the host after infection, leading to cellular homeostasis imbalance and tissue damage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Manifestasi infeksi ASF menghasilkan 4 bentuk gejala klinis seperti perakut, akut, subakut dan kronis, tergantung dari virulensi strain yang menginfeksi, strain babi dan status kekebalan (Sanchez-Vizcano et al 2015). Umumnya, babi liar seperti babi hutan lebih rentan terhadap infeksi ASF dan tidak menimbulkan gejala klinis yang khas, namun dapat bertindak sebagai karier virus ASF (Cabezón et al 2017).…”
Section: Manifestasi Klinis Asfunclassified